Investigating the effects of confining pressure and loading rate on damage propagation and mode I stress intensity factor of granite using the RHT constitutive model - Hooman Rouhani; Mehdi Arash; Ebrahim Farrokh (Geomechanics and Geophysics for Geo-Energy and Geo-Resources)
Abstract This study explores influence of confining pressure and loading rate on the mode I stress intensity factor (SIF) and damage propagation rate in cracked straight-through Brazilian disc (CSTBD) specimens. Driven by need to improve material reliability in applications like geotechnical and structural engineering, where diverse loading conditions prevail, research utilizes a calibrated Riedel-Hiermaier-Thoma constitutive model. The model’s predictive accuracy was confirmed through triaxial, Brazilian tensile, and dynamic tensile tests. Simulations of CSTBD specimens under static and dynamic conditions were conducted using a finite element Lagrangian code with an erosion model, validated against experimental data. Maximum applied stress rises with increasing stress rate and confining pressure, while mode I SIF decreases under higher confinement, suggesting crack closure. Loading rate impacts mode I SIF in a manner consistent with maximum stress trends. Confining pressure suppresses crack propagation, with cracks under high pressure growing perpendicularly and yielding negative mode I SIF values. Both maximum Damaged zone length and damage propagation rate diminish as confining pressure increases, reducing damage spread. These insights are critical for designing robust structures under confinement, such as pressure vessels or underground systems, by demonstrating how confining pressure curbs crack growth, thereby enhancing material durability and safety.